Factors Determining Rural Youth Participation in Agriculture-Based Livelihood Activities: A Case Study of Karsog in Himachal Pradesh - Chaudhary, Rashmi; Janjhua, Yasmin; Sharma, Nikhil; Sharma, Deepika; Pathania, Ankit; Kumar, Krishan (International Journal of Economic Plants, 2019)
Engagement of rural youth in agriculture based livelihood activities is gaining attention as a strategy to mitigate current problem of unemployment due to employment potential of these activities. Nonetheless, there have been evidences about declining youth participation in agriculture based livelihood activities. The present study investigated the factors determining rural youth participation in agriculture based livelihood activities. Examination of a sample of 250 youth respondents identified; agricultural knowledge, availability of land, interest in agriculture, fertile soil, favourable environment & temperature, availability of different types of soil, good transportation facilities and well connectivity as some of the factors determining rural youth participation in agriculture-based livelihood activities in the study area. The overall results for predominant agricultural based activities in which youth participate indicates that youths in the study area are not significantly engaged in agriculture based livelihood activities. However crop farming and livestock rearing are the two major activities in which they are involved. The results of the study will have some useful implication for the policy makers and it is recommended that all stakeholders must make efforts to create favourable environment for increasing youth participation in agriculture based livelihood activities.